Dukungan Jepang Dalam Melawan Terorisme Era Pemerintahan Koizumi 2001-2006 - Freitas, Abilio Tedja Da Silva (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRACT The purpose of this research is explain the role and interest of Japan on United State’s war on terrorismbetween 2001-2006. Japan is one country that has always played an active role in helping the United States in the United States campaign against terrorism since 20 century. It is based on the defeat of the Japanese during the second world war that the in the present, Japan have a dependency in military terms with the United States. In this condition, Japan want to pursue its interest for maintaining the military cooperation with the United State. In this case, I put more emphasis on the effort and interest by japan on maintaining their goal. Keywords : war on terrorist, interest, military cooperation